2017
DOI: 10.1002/hipo.22740
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise reduces hippocampal ERK and p38 activation and improves memory of middle‐aged rats

Abstract: Aging is often accompanied by cognitive decline, memory impairment, and an increased susceptibility to neurodegenerative disorders. Although the physiological processes of aging are not fully understood, these age-related changes have been interpreted by means of various cellular and molecular theories. Among these theories, alterations in the intracellular signaling pathways associated with cell growth, proliferation, and survival have been highlighted. Based on these observations and on recent evidence showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
2
6
1
Order By: Relevance
“…The current finding is in accordance with the proposal that both Ns- and exercise-induced cardiac hypertrophies are physiological forms of cardiac hypertrophy. The reduction of Erk1/2 was also reported in the hippocampal tissue of trained rats [ 36 ]. However, since our trained rats demonstrated an increase in AT-1 and endothelin-1, then the reduction in Erk1/2 might be visualized as an unexpected finding.…”
Section: Discussionsupporting
confidence: 55%
“…The current finding is in accordance with the proposal that both Ns- and exercise-induced cardiac hypertrophies are physiological forms of cardiac hypertrophy. The reduction of Erk1/2 was also reported in the hippocampal tissue of trained rats [ 36 ]. However, since our trained rats demonstrated an increase in AT-1 and endothelin-1, then the reduction in Erk1/2 might be visualized as an unexpected finding.…”
Section: Discussionsupporting
confidence: 55%
“…Further, a randomized controlled trial in older adults demonstrated changes in brain activity in specific brain regions with exercise training(11). Other studies, in animals and young adults, support this finding and indicate that exercise can induce changes in the hippocampus(810). In mice, running enhanced hippocampal neurogenesis and learning(9).…”
Section: Exercise and Cognitive Functionsupporting
confidence: 57%
“…In mice, running enhanced hippocampal neurogenesis and learning(9). In rats, treadmill running reduced activation of inflammatory signaling pathways in the hippocampus and resulted in better cognitive performance(10). Hippocampal changes are specifically relevant to dementia, as it is important in memory processes and has been of specific focus in the study of Alzheimer’s disease(17) Studies have also shown preservation of both white and gray matter with increased exercise(1215).…”
Section: Exercise and Cognitive Functionmentioning
confidence: 99%
“…EE-induced modification in hippocampal glutamatergic (Mlynarik et al 2004;Naka et al 2005;Segovia et al 2006;Andin et al 2007), cholinergic Savage 2016), GABAergic (Frick et al 2003;Segovia et al 2006), norepinephrinergic (Galani et al 2007) and serotonergic (Rasmuson et al 1998;Galani et al 2007;Pang et al 2009) transmission have also been reported. Likewise, alterations in the expression of proteins related to hippocampal ERK, CREB, PKA, PKC, CAMKII, MAPK signaling have also been noted in rodents exposed to EE (Shen et al 2001;Williams et al 2001;Zhang et al 2016a;Cardoso et al 2017). Given that these signaling molecules play critical roles in synaptic plasticity (Malinow et al 1989;Meffert et al 1991;Schulman 1995;Lisman et al 2002) and addiction-related behaviors (Ortiz et al 1995;Levine et al 2005;Lu et al 2006;Lee and Messing 2008) and can be altered by environmental experiences, it is reasonable to suggest that EE, by providing multidimensional stimulation, rewires hippocampal-centered circuits, generates new connections that augment the values of non-drug rewards while weakening the values of drug-based memories.…”
Section: Effects Of Ee On the Hippocampusmentioning
confidence: 94%